PERCONTOHAN JAMBAN KELUARGA SEHAT DI KELURAHAN KAYUMALUE NGAPA KECAMATAN PALU UTARA KOTA PALU - Djaafar, Tjitrowati; Hasanudin, Hasanudin; Saharudin, Saharudin (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
Poor sanitation is one of the main factors causing disease in Indonesia. Kayumalue Ngapa Village, North Palu, Palu City, is one of the areas with low levels of access to sanitation. Many families in this neighbourhood do not have healthy and proper latrines. This causes various health problems, such as diarrhoea, skin diseases, and worms. This community service aims to build healthy family latrines through mentoring, improve access to sanitation and public health, and improve their quality of life. The methods of this community service activity include: socialisation and education of the results of community service on healthy family latrines, construction of healthy family latrines, and monitoring and evaluation. The results of this activity are the construction of 1 healthy family latrine as a pilot, increasing access to sanitation and public health, and improving their quality of life. The construction of healthy family latrines can improve access to sanitation and community health, and improve their quality of life.